THE EFFECT OF AUDIT ROTATION, AUDITOR COMPETENCE, AND CLIENT PRESSURE ON AUDITOR INDEPENDENCE - Aerindea Hertametia Antonio; Ni Luh Sari Widhiyani (Adisam Publisher, 2025)
Auditor independence is an important factor in maintaining the quality, objectivity and credibility of audit results, so it is very important for public trust in financial statements. This study aims to examine the effect of audit rotation, auditor skills, and pressure from clients on the level of auditor independence. The study used an associative quantitative approach with primary data obtained through distributing questionnaires to 47 auditors who work at public accounting firms (KAP) in Bali Province, based on the IAPI Directory in 2024. The analysis method used is multiple linear regression. The results showed that audit rotation and auditor skills have a positive and significant effect on auditor independence, while client pressure has a negative and significant effect. This finding is in line with the Interpersonal Behavior Theory, Resource-Based Theory, and Challenge-Hindrance Stressor Framework, especially on Hindrance Stressor, which emphasizes the importance of individual factors and professional pressure in influencing auditor behavior. This research provides practical and theoretical contributions and serves as a reference for future studies in the field of auditing.